Pengaruh Literasi Ekonomi terhadap Niat Berwirausha melalui Motivasi dan Self Efficacy sebagai Variabel Mediasi - Anggista, Melliana Dian; Fitrayati, Dhiah (Inspirasi Nusantara, 2023)
In an era of high population growth and increasing unemployment, a deep understanding of entrepreneurship accompanied by motivation and self-confidence can influence individual intentions for entrepreneurship. This research aims to determine the effect of economic literacy on entrepreneurial intentions through motivation and self-efficacy as mediation with the Stimulus-Organism-Response approach in FEB Unesa students 2020-2021. Samples in this study were 284 students from 9 FEB Unesa study programs. The data analysis technique used in this study is the SEM approach and the PLS analysis equation model using WarpPLS software version 8.0. The research results showed that the economic literacy variable had a positive and significant effect on entrepreneurial intentions. Economic literacy variables have a positive and significant although weak impact on motivation. Economic literacy variables have a positive and significant effect on self-efficacy. Economic literacy variables positively and significantly affect entrepreneurial intentions through motivation. Economic literacy variables positively and significantly affect entrepreneurial intentions through self-efficacy. Economic literacy variables positively and significantly affect entrepreneurial intentions through motivation and self-efficacy.